Prediction of Travel Time Using Fuzzy Logic Paradigm - AJASA, ABIODUN AFIS; I. I., Ajayi,; K. D., Akinwande,; T.O., Ajayi, (Discoveries in Agriculture and Food Sciences, 2019)
Predicting travel time is an important aspect of human life. It helps to effectively manage and successfully make the most of time. So much time is usually spent on the road when travelling from one place to another, particularly in developing countries and in a mega city like Lagos for example, a little time wasted is a lot of money lost, hence the need to envisage the likely time to reach destinations. This research work explores the robustness of fuzzy logic to predict travel time on all major routes out of the town where the Engineering faculty of Lagos State University is situated. This paper takes into consideration important factors that can lead to delay in travel time; period of day, weather, car density, and construction, as the fuzzy inputs and based on experience, fuzzy rules are generated to give an estimated time of arrival. To prove the validity of this work, data were collected from frequent road users and co-efficient of determination was calculated for all three routes. The co-efficient of determination ranked above 90% for all three routes, two of which are discussed.